beta-Glucan Increases IFN-gamma and IL-12 Production of Peripheral Blood Mononuclear Cells with/without Induction of Mycobacterium tuberculosis Wild-type/Mutant DNA - Meira Erawati; Nyoman Suci Widyastiti; Tri Indah Winarni; Edi Dharmana (The Indonesian Biomedical Journal, 2019)
BACKGROUND: In tuberculosis infections, the immune system is weakened and cannot produce enough cytokines to against the infection. b-glucan is a potent immunomodulator that induces cytokine production in various bacterial infections. This study aimed to determine the effects of b-glucan on the production of interferon (IFN)-γ and interleukin (IL)-12 in peripheral blood mononuclear cells (PBMCs) induced by Mycobacterium tuberculosis DNA.METHODS: PBMCs were isolated from 11 healthy subjects. PBMCs were treated with/without 5 μg/mL b-glucan and M. tuberculosis rpoB wild-type or mutant DNA. The production of IFN-γ and IL-12 in the supernatant was performed with enzyme-linked immune-sorbent assay (ELISA).RESULTS: b-glucan increased significantly (p<0.05) IFN-γ of M. tuberculosis mutant DNA-induced PBMCs, M. tuberculosis wild-type DNA-induced PBMCs, and non-induced PBMCs. b-glucan also increased significantly (p<0.05) IL-12 of M. tuberculosis mutant DNA-induced PBMCs, M. tuberculosis wild-type DNA-induced PBMCs, and non-induced PBMCs. There were not any significant difference between male and female groups for IL-12 and IFN-γ in all treatment groups (p>0.05, ANOVA test).CONCLUSION: This in vitro study indicates that b-glucan increases the performance of PBMCs to produce IFN-γ and IL-12, with/without induction of M. tuberculosis wild-type/ mutant DNA.KEYWORDS: b-glucan, IFN-γ, IL-12, M. tuberculosis, rpoB